Riluzole use in presence of contraindications in adults affected by amyotrophic lateral sclerosis and its off-label use in other motor neuron diseases: Findings from an Italian multicentre study (the CAESAR project) - Crescioli, Giada; Finocchietti, Marco; Cascini, Silvia; Paoletti, Olga; Franchini, David; Cappello, Emiliano; Valdiserra, Giulia; Sciancalepore, Francesco; Celani, Maria Grazia; Tuccori, Marco; Vannacci, Alfredo; Lombardi, Niccolò; et al. (Frontiers in Drug Safety and Regulation, 2022)
Background: This analysis describes the use of riluzole in amyotrophic lateral sclerosis (ALS) individuals with contraindications and off-label use for subjects with other motor neuron diseases (o-MND) in the Italian regions of Latium, Tuscany and Umbria. Methods: A cohort of adults with ALS prescribed with riluzole during the years 2016–2019 was enrolled from administrative healthcare databases, excluding subjects with o-MND in the preceding 5 years. Being affected by ALS for more than 5 years, presence of tracheostomy, renal or hepatic failure were considered as contraindications to the use of riluzole. A cohort of adults with o-MND was enrolled in 2016–2019 for whom off-label use of riluzole was retrieved up to 4 years, analysing over the time differences related to sex. Results: Among 206 ALS individuals prescribed with riluzole in Latium, 336 in Tuscany and 60 in Umbria, less than 1% were diagnosed with ALS for more than 5 years. Less than 2% were tracheotomised or affected by hepatic failure. Renal failure was documented for 1.9%, 2.7%, and 5.0% of ALS individuals in Latium, Tuscany and Umbria. The o-MND cohort comprised 264 subjects in Latium, 222 in Tuscany, and 66 in Umbria. Non-negligible off-label riluzole use was observed: 8.5%, 33.0%, and 4.2% in females, and 19.9%, 26.5% and 2.4% in males in Latium, Tuscany and Umbria. Discussion: Riluzole use in ALS individuals in the presence of contraindications is rare, with slightly higher numbers in presence of renal failure. Off-label use in o-MND was found to be non-negligible, with variations between sexes.